Stable School Integration? - Francis, Dania V. (Race and social problems, 2023)
As public school districts across the country are released from their mandatory school desegregation orders, there has been increasing examination of the re-segregation of public schools. By contrast, little attention has been paid to schools that are becoming more integrated and whether stable racial integration exists in public schools. Using National Center for Education Statistics Data on school demographic composition of all schools across the country, we identify racially integrated schools, examine the stability of the integrated composition of these schools across a twenty-year period (1995–2015), and then describe the characteristics of these integrated schools. We find that an increasing share of schools are integrated, but that this is driven by an increase in Asian/White and Hispanic/White integrated schools, while the number of Black/White integrated schools declines.